Determination of visual acuity and visual axis of brown-marbled grouper, epinephelus fuscoguttatus to develop a demand feeding system - Han Tan, Nai; Mukai, Yukinori; Firdaus, Rian Freddie (Universiti Malaya, 2013)
The visual acuity and visual axis of juvenile brown-marbled grouper, Epinephelus fuscoguttatus were determined to get the understanding of their vision in order to develop a demand feeding system. Three juveniles were anaesthetised with MS222 and fixed in Bouin’s solution. The left retina of each juvenile was cut into nine regions – the dorso-nasal (DN), dorsal (D), dorso-temporal (DT), nasal (N), bottom (B), temporal (T), ventro-nasal (VN), ventral (V), and ventro-temporal (VT). The specimens were embedded in paraffin, cut into 6 μm thick tangential sections, and stained with haematoxylin-eosin. The density of cone cells (0.01 mm2) in each region was counted in the stained sections. Visual acuity was calculated using cone cell densities and lens diameter. The highest cone cell densities of each of the juveniles were 359 (bottom, B), 394 (temporal, T), and 380 cells/0.01 mm2 (temporal, T), respectively. The estimated visual acuities were 0.068-0.081 in those regions, respectively. These results showed that the visual axis of brown-marbled grouper juveniles was forward. Therefore, the position of the target switch of demand feeding system was set at 2 cm below the water surface.